Naringenin Modifies the Development of Lineage-Specific Effector CD4+ T Cells - Wang, Junpeng; Niu, Xinli; Wu, Chunfang; Wu, Dayong (Frontiers in Immunology, 2018)
Disrupted balance in the lineages of CD4+ T cell subsets, including pro-inflammatory T helper (Th) cells and anti-inflammatory regulatory T cells (Treg), is a primary pathogenic factor for developing autoimmunity. We have found that this immunomodulatory effect of naringenin on effector T cells and T-cell mediated experimental autoimmune encephalomyelitis. We therefore explored the effects of naringenin on the development of different effector CD4+ T cells. Naïve CD4+ T cells were differentiated under respective Th1, Th2, Th17, and Treg polarizing conditions with naringenin. Percent populations of each differentiated CD4+ T cell subsets were determined and the corresponding regulating pathways were investigated as underlying mechanisms. Naringenin mainly inhibited CD4+ T cell proliferation and differentiation to Th1 and Th17, but did not affect Th2 cells. Impeded Th1 polarization was associated with inhibition of its specific regulator proteins T-bet, p-STAT1 and p-STAT4 by naringenin. Likewise, Th17 regulator proteins RORγt, p-STAT3 and Ac-STAT3 were also inhibited by naringenin. In addition, naringenin promoted Treg polarization and also prevented IL-6-induced suppression of Treg development via down-regulation of p-Smad2/3 as well as inhibition of IL-6 signaling, and the latter was further supported by the in vivo results showing lower soluble IL-6R but higher soluble gp130 levels in plasma of naringenin-fed compared to the control EAE mice. Naringenin impacts CD4+ T cell differentiation in a manner that would explain its beneficial effect in preventing/mitigating T cell-mediated autoimmunity.